Surface Roughness Effect on Porous Pivoted Slider Bearings with Squeeze Film Formed by Couple Stress Fluid - Kashinath, B.; Upadhya, A. C. (Journal of Scientific Research, 2025)
The study intends to investigate the problem of surface roughness effects on porous pivoted slider bearings with squeeze film formed by couple stress fluid. On the basis of the micro continuum theory, the modified Reynolds’ type equation of porous slider bearing is obtained by considering rough surface and squeezing action. The closed-form expressions for the mean pressure, load carrying capacity, frictional force and centre of pressure are obtained. Capacity for load bearing and point where pressure is centred are evaluated in form of various parameters that are couple stress, permeability and surface roughness. It is concluded that capacity for load bearing increases with roughness and decreases with increase in permeability parameters. Normal behaviour of exists for surface roughness parameters with pressure and pressure with permeability parameters. Computed values of load capacity, frictional force and coefficient of friction are displayed in graphical form.